2017
DOI: 10.1159/000452492
|View full text |Cite
|
Sign up to set email alerts
|

Neohesperidin Exerts Lipid-Regulating Effects in vitro and in vivo via Fibroblast Growth Factor 21 and AMP-Activated Protein Kinase/Sirtuin Type 1/Peroxisome Proliferator-Activated Receptor Gamma Coactivator 1α Signaling Axis

Abstract: The purpose of this study is to prove the lipid-regulating effects of neohesperidin (NHP) and explore the potential mechanisms related to fibroblast growth factor 21 (FGF21) and AMP-activated protein kinase (AMPK). Free fatty acids (FFAs)-induced lipid-accumulated HepG2 cells, acutely egg yolk-induced dyslipidemia and chronically diet-induced obese (DIO) model mice were treated with NHP. Biochemical analyses were carried out to determine the lipid profiles. Western blotting and real-time PCR were em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 41 publications
0
24
0
Order By: Relevance
“…Oliva and co‐workers demonstrated that the chronic treatment of NRG in ethanol‐fed male Wistar rats increased SIRT1 at both gene and protein level (Oliva et al, ). NHP was found to enhance the expression of SIRT1 both in vitro and in vivo, in free fatty acids‐induced lipid‐accumulated HepG2 cells and chronically diet‐induced obese (DIO) model mice, respectively (Wu et al, ). Regarding HSP and NER, this is the first report on their effect on SIRT1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oliva and co‐workers demonstrated that the chronic treatment of NRG in ethanol‐fed male Wistar rats increased SIRT1 at both gene and protein level (Oliva et al, ). NHP was found to enhance the expression of SIRT1 both in vitro and in vivo, in free fatty acids‐induced lipid‐accumulated HepG2 cells and chronically diet‐induced obese (DIO) model mice, respectively (Wu et al, ). Regarding HSP and NER, this is the first report on their effect on SIRT1.…”
Section: Resultsmentioning
confidence: 99%
“…Some flavonoids assessed here have been studied for their properties on activating AMPK pathway. The treatment with NAR (Zygmunt, Faubert, MacNeil, & Tsiani, ), NRG (Sui, Xiao, Lu, & Sun, ), or NHP (Wu et al, ) was shown to positively act on AMPK both in vitro and in vivo models. HSP and NER were not investigated in these regards.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, the expression of liver PGC-1α increased significantly after CA consumption and a combination of aerobic training and CA. The results of a study showed that the glycosidase flavonoid in citrus fruits can activate the AMPK-SIRT1-PGC-1α pathway and thus play a role in controlling fat metabolism (29). Naringin has also been shown to increase PGC-1α, CPT1 and adiponectin expression (30).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms by which chronic intake of hesperidin may improve performance are associated with increased activation of AMP-activated protein kinase (AMPK) [19,20] and nuclear respiratory factor 2 (NRF2) [6], leading to improved mitochondrial biogenesis and antioxidant status, respectively [21,22]. In addition, hesperidin has the ability to improve nitric oxide synthesis (NO) [23], which may improve glucose utilization in exercise and increase blood flow to the muscles, promoting an increase in nutrient and oxygen delivery to the muscle [24].…”
Section: **Insert Figure 1**mentioning
confidence: 99%